2019
DOI: 10.5888/pcd16.190165
|View full text |Cite
|
Sign up to set email alerts
|

Agua4All: Providing Safe Drinking Water in Rural California Communities

Abstract: IntroductionDrinking water instead of sugar-sweetened beverages may reduce obesity and dental caries. Tap water is more affordable and sustainable than bottled water and more likely to contain fluoride, which prevents caries. To address inequities in access to safe tap water, cross-sector partners established the Agua4All safe drinking-water program in 2 rural San Joaquin Valley, California, communities. The program’s objective was to examine Agua4All’s feasibility, acceptability, and effect on water intake.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, to substantially impact SSB intake, the promotion of tap water as a replacement for SSBs may be needed (Moghadam et al 2019). Previous studies in other community settings suggest that coupling appealing water sources with promotional activities, such as signage, can significantly increase water intake (Patel et al 2019;Lawman et al 2020). Despite the importance of promotion efforts, no parks in this study marketed tap water via posters, signage, or other materials.…”
Section: Discussionmentioning
confidence: 86%
“…However, to substantially impact SSB intake, the promotion of tap water as a replacement for SSBs may be needed (Moghadam et al 2019). Previous studies in other community settings suggest that coupling appealing water sources with promotional activities, such as signage, can significantly increase water intake (Patel et al 2019;Lawman et al 2020). Despite the importance of promotion efforts, no parks in this study marketed tap water via posters, signage, or other materials.…”
Section: Discussionmentioning
confidence: 86%
“…In the interview analysis, we had difficulty teasing out whether changes were due to the campaign, the water-bottle filling stations, or some combination of the two. Patel’s et al (2019); Schwartz’s (2016) studies found that increased water access at school is linked to increased water consumption and to body mass index changes. However, other studies have shown that additional education and training are necessary to maximize impacts (James et al, 2004; Patel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%